PELATIHAN BAHASA INGGRIS MENGGUNAKAN KONTEN "ONLINE DICTATION" DI WEBSITE WWW.ENGLISHCLUB.COM KEPADA CALON PEKERJA CRUISE SHIP - surip Haryani (ABDIMAS Madani, 2021)
THE ENGLISH TRAINING USING ONLINE DICTATION”CONTENT IN WWW.ENGLISHCLUB.COM WEBSITE FOR CRUISE SHIP WORKER CANDIDATE Candidate of workers who look for a job abroad ara generally trying hard to improve their abilities in mastering theri english proficiencey. Based on a preliminary study conducted to pre-worker group in Kotabaru Jogjakarta, it was found that some of them were preparing to work in a cruise ship abroad. They were studying English and they got free training from volunteers. The training was given un a form of dictation listening activity using Önline Dictation”content in www,englishclub.com website. The training was given to a group of pre-workers graduated from Senior High School and College. They were in a wait list to work in a cruise ship abroad. The training was given in a form of lecture, stimulation and practice. It was conducted on Januari 14, 2021 at Jl. Patimura Yogyakarta. There were 22 participants joining the training anthusiastically. The team gave a stimulation by playing listening audio with normal and slow versions of the speech. The two versions played once and the participants wrote what they listened in the audio during the slow versions played. The topic of the dictation includes in the basic and intermediate levels. At the end of the session the participants were given refrence resources and audio format for them to do self study. It is hoped that the participants can study and practice the dictation technique to improve their ability in listening skill independently. Keywords:, English, Dictation, Listening, Training